Analisis Kebijakan Pemerintah Daerah dalam Mencegah Timbulnya Penyakit HIV-AIDS Pemerintah Kabupaten Jember - Rafel Destrio, Yosvico (Indonesian Journal Publisher, 2025)
This study aims to analyze the Jember District Government's policy in preventing the spread of HIV/AIDS, a health issue that continues to pose a serious threat both nationally and globally. Jember District recorded a significant number of HIV/AIDS cases by 2024, thus encouraging the local government to implement various prevention policies and programs. This study uses a qualitative approach with descriptive methods through observation and documentation to evaluate the effectiveness of local policies, identify barriers, and formulate alternative solutions. The results show that prevention policies have been implemented through the provision of health services, educational campaigns, and collaboration with NGOs and international organizations. However, challenges such as social stigma, budget constraints, lack of community participation, and lack of inter-agency coordination remain major obstacles. This study highlights the importance of a community-based approach involving community leaders and religious leaders in education and stigma reduction efforts. More innovative, inclusive and sustainable strategies are needed to improve policy effectiveness, including strengthening coordination between agencies and developing programs based on local values. This research is expected to serve as a reference for more comprehensive policy development in other regions facing similar challenges.